1988
DOI: 10.1680/macr.1988.40.143.79
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vibration on the rheological properties of fresh concrete

Abstract: Synopsis Using a set-up in which the bowl of a two-point workability test apparatus was mounted on an electro-magnetic vibrating table, measurements were made on unvibrated fresh concrete and on the same samples under vibration. It was shown that when vibration is applied the flow properties of fresh concrete are no longer represented by the simple linear Bingham model but approximate to those of a power law pseudoplastic with zero yield value. At very low shear rates behaviour approximates to that of a Newto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1
2

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 0 publications
1
30
1
2
Order By: Relevance
“…Practically, vibration appears to remove the yield stress of fresh concrete, which then flows under its own weight [234,235] and the important characteristic of the vibration is the peak velocity. The fluidity of vibrated concrete, defined as the reciprocal of its low shear rate viscosity, is proportional to peak vibrational velocity up to a critical value, above which it is constant, and the viscosity of the vibrated concrete is proportional to the plastic viscosity of the unvibrated concrete [236].…”
Section: Vibrational Compactionmentioning
confidence: 99%
“…Practically, vibration appears to remove the yield stress of fresh concrete, which then flows under its own weight [234,235] and the important characteristic of the vibration is the peak velocity. The fluidity of vibrated concrete, defined as the reciprocal of its low shear rate viscosity, is proportional to peak vibrational velocity up to a critical value, above which it is constant, and the viscosity of the vibrated concrete is proportional to the plastic viscosity of the unvibrated concrete [236].…”
Section: Vibrational Compactionmentioning
confidence: 99%
“…Vibration will remove or reduce the yield stress, but has no effect on viscosity [3,4]. However, fresh concrete is a particle assembly and the particle character is non-negligible.…”
Section: Introductionmentioning
confidence: 99%
“…The yield stress and plastic viscosity are not constant and dependent on the particle fabric [5]. Tattersall et.al [4,6] first attempt to measure the rheology of vibrated fresh concrete with a two-point rheometer located on an electromagnetic vibrating table. It is shown that vibrated fresh concrete is a kind of power law pseudoplastic body with zero yield stress, its rheological behaviors are no longer represented by Bingham model.…”
Section: Introductionmentioning
confidence: 99%
“…During placement and compaction, fresh concrete is usually vibrated or tapped to make it flow more easily. Under vibration, there is a significant reduction in the yield stress [3][4][5] and a decrease in its viscosity. 3 The presence of a yield stress in a medium retards, and may even prevent, the natural settlement of heavier solids in it.…”
Section: Introductionmentioning
confidence: 99%
“…Under vibration, there is a significant reduction in the yield stress [3][4][5] and a decrease in its viscosity. 3 The presence of a yield stress in a medium retards, and may even prevent, the natural settlement of heavier solids in it. 6 A solid may or may not sink in a medium, depending on the size of the solid, the magnitude of the yield stress of the medium, and the density difference between the solid and the medium.…”
Section: Introductionmentioning
confidence: 99%